Amazonian phylogeography: Mtdna sequence variation in arboreal echimyid rodents (caviomorpha) - Silva, Maria Nazareth Ferreira da; Patton, James L. (Molecular Phylogenetics and Evolution, 1993)
Patterns of evolutionary relationships among haplotype clades of sequences of the mitochondrial cytochrome b DNA gene are examined for five genera of arboreal rodents of the Caviomorph family Echimyidae from the Amazon Basin. Data are available for 798 bp of sequence from a total of 24 separate localities in Peru, Venezuela, Bolivia, and Brazil for Mesomys, Isothrix, Makalata, Dactylomys, and Echimys. Sequence divergence, corrected for multiple hits, is extensive, ranging from less than l% for comparisons within populations of over 20% among geographic units within genera. Both the degree of differentiation and the geographic patterning of the variation suggest that more than one species composes the Amazonian distribution of thecurrently recognized Mesomys hispidus, Isothrix bistriata, Makalata didelphoides, and Dactylomys dactylinus. There is general concordance in the geographic range of haplotype clades for each of these taxa, and the overall level of differentiation within them is largely equivalent. These observations suggest that a common vicariant history underlies the respective diversification of each genus. However, estimated times of divergence based on the rate of third position transversion substitutions for the major clades within each genus typically range above 1 million years. Thus, allopatric isolation precipitating divergence must have been considerably earlier than the late Pleistocene forest fragmentation events commonly invoked for Amazonian biota. © 1993 Academic Press.
Keywords: Cytochrome B; Dna, Mitochondrial; Primer Dna; Animals; Chemistry; Classification; Comparative Study; Genetic Variability; Genetics; Geography; Liver Mitochondrion; Metabolism; Molecular Genetics; Nucleotide Sequence; Phylogeny; Rodent; Species Difference; Animals; Base Sequence; Comparative Study; Cytochrome B; Dna Primers; Dna, Mitochondrial; Geography; Mitochondria, Liver; Molecular Sequence Data; Phylogeny; Rodentia; Species Specificity; Support, Non-u.S. Gov't; Support, U.S. Gov't, Non-p.H.S.; Variation (genetics)